STRATEGI EFEKTIF UNTUK MENCEGAH BULLYING DI LINGKUNGAN SEKOLAH - Alfini Liansi; Zhyka Tirta Wardani Wardani; Mustakim Mustakim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Bullying is a serious problem that frequently occurs in schools and negatively impacts students' psychological, social, and academic development. To address this issue, Madako University Tolitoli Community Service (KKN) students implemented a community service program entitled